2021
DOI: 10.1155/2021/5590470
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Tutoring System: Learning Math for 6th-Grade Primary School Students

Abstract: This paper proposes a web-based application designed to help elementary school students who have difficulty learning online independently and also their parents who are currently having difficulty teaching their children to study at home online, especially at this time of difficulty with a pandemic outbreak like COVID-19; this time does not allow for physical meetings for the learning process in primary schools. In this paper, we only focus on mathematics because based on several other studies, it is very diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Intelligent tutoring systems (ITS) is an AI application in education that provides self-paced learning giving instant feedback to students. King et al (2021) utilised an ITS to help students learn mathematics and reported that the AI technique improved students' learning outcomes as well as their attitudes toward mathematics. Students who used the ITS performed better on tests than those who did not, demonstrating that AI is a useful tool for enhancing students' learning.…”
Section: Improve Learning Outcomementioning
confidence: 99%
“…Intelligent tutoring systems (ITS) is an AI application in education that provides self-paced learning giving instant feedback to students. King et al (2021) utilised an ITS to help students learn mathematics and reported that the AI technique improved students' learning outcomes as well as their attitudes toward mathematics. Students who used the ITS performed better on tests than those who did not, demonstrating that AI is a useful tool for enhancing students' learning.…”
Section: Improve Learning Outcomementioning
confidence: 99%
“…To be more specific, for senior high school, this understanding is lacking. Several studies argue that the implementation of Math application is centered around primary education (King et al, 2021;Pramana et al, 2021;Rachmavita, 2020) and higher education (Fuady et al, 2021;Syarif et al, 2021). There are studies of the implementation of math application in secondary level, however, it is more to junior high school level (Adnan & Anwar, 2020;Nida et al, 2020;Sumardi et al, 2021).…”
Section: Students' Suggestions About Ai-based Learning In Mathematics...mentioning
confidence: 99%
“…However, the topic was limited to only one small topic -the rules of filling slot in the field of probability. Another study conducted by King et al (2021) has also implemented CTAT but limited to a simple web-based application that allows teachers to upload modules to be learned by students. In other words, the adaptation of AI-based learning in mathematics education in Indonesia is still lacking.…”
mentioning
confidence: 99%
“…Dampak ini dirasakan juga pada pada bidang pendidikan (Hambali et al, 2021;Mithhar et al, 2021) dan pembelajaran di sekolah dasar. Selama Pandemi Covid-19, sekolah ditutup dan sangat dibatasi untuk pertemuan tatap muka secara langsung (Friskawati et al, 2021;King et al, 2021). Kebijakan tersebut mendorong agar siswa belajar dari rumah dengan metode pembelajaran secara virtual (Rafiqa et al, 2021;Yulianti & Mukminin, 2021).…”
Section: Pendahuluanunclassified